Keratin 20 positive SDH-deficient renal cell carcinoma: a case report and literature review - Shuang-Shuang Dong; Zong-Yue Wang; Xiu-Chun Tian; Cui-Mei Wang; Qing Xu; Chen Xu; Wei Yang; Xue-Wen Gu; Qin Xiao (BMC, 2024)
Abstract This study aims to broaden the morphological scope of SDH-deficient renal cell carcinoma and to assist clinicians and pathologists in better understanding this entity to prevent misdiagnosis. This study used immunohistochemistry staining and the first-generation sequencing Sanger method for gene detection. It retrospectively analysed the clinical pathology, molecular characteristics, biological behaviour, and treatment information of one case of SDH-deficient renal cell carcinoma. The patient was a 57-year-old female with right back pain for more than 20 days and had no personal or family history of kidney tumours. In addition, the tumour cells had clear boundaries in morphology, and residual normal renal tubules could be seen around them. There were also ossification and adipose tissue around the tumour centre. The tumour cells were arranged in a glandular tubular and cord-like manner. Vacuolar and eosinophilic inclusion bodies could be observed in the cytoplasm. The nucleus was regular, the chromatin distribution was fine, and there were no obvious nucleoli. They were low-grade nuclei. In addition, no atypical mitosis or necrosis could been found. Furthermore, immunohistochemistry staining showed SDHB-negative and keratin 20 -positive tumour. Meanwhile, the first-generation sequencing also pointed out the presence of SDHB gene mutations in the tumour. After 12 months of follow-up, there was no evidence of disease recurrence in the patient. SDH-deficient renal cell carcinoma is a rare tumour associated with SDH gene germline mutations, and suspected cases should undergo SDHB immunohistochemistry staining. Most SDH-deficient renal cell carcinomas have a good prognosis, but undifferentiated cases require long-term follow-up.